A Corruption Course through a Culturally Relevant Pedagogy: The Need for an Assessment That Fits - Khadija El Alaoui; Maura A. E. Pilotti (MDPI AG, 2021)
The present study examines the challenges and the rewards of assessing learning in a seminar on corruption which is taught in a country (Iraq) where political corruption is seen as the main source of structural instability and sectarian tensions. It specifically focuses on the role of culturally relevant pedagogy in defining the most suitable summative assessment. To this end, essay test questions were developed concerning the relevance of political corruption, the impact of investigative journalism, the role of humor in investigative journalism, and the appropriate remedies (besides journalism) to political corruption. In students' responses, investigative journalism (with or without humor) was consistently reported to be a dangerous undertaking, but disagreement emerged on its effectiveness as one of the possible remedies for corruption. Dishonesty was seen as the universal cancer of political systems and thus difficult to extirpate, albeit some systems (e.g., Al-Muhasasa) were seen as tolerating it more than others. In our study, the qualitative examination of students' responses served three objectives: (a) it offered evidence about the extent to which culturally relevant pedagogy was realized in the course; (b) it served to put forth a proposal on how students' test responses can inform teaching and assessment in future offerings of the course; and more broadly, (c) it synopsized the views of a sample of college students who represent the population upon whom the country heavily relies for its economic and political recovery.